INVENTARIO PALINOLÓGICO DE LA UNIVERSIDAD INDUSTRIAL DE SANTANDER - Jerez-Jaimes, Javier Hernando; Narváez-Parra, Eliana Ximena (Innovaciencia, 2016)
Introduction: Palynology plays an important role in the resolution of ecological, geological, paleontological, medical and environmen- tal problems, for this reason the inclusion of practical strategies that introduce students in this field of research are necessary in the pro- grams of Geology, Biology and Health Sciences. In this sense, the availability of pollen inventory facilitates and promotes the learning. Methods: The plant material was collected in the period from March to April 2011 on the campus of the Universidad Industrial de Santand- er (Bucaramanga: Colombia). Pollen and spores were extracted with dissecting needles and fixed with xylol on slides, subsequently were observed under the optical microscope and photographed. Pollen were classified according to the form and the unit. Results and Discussion: 25 species in 19 families of plants were analyzed, with this infor- mation the palynological inventary of the Universidad Industrial de Santander was elaborated. The purpose of this inventary is clearly introductory and support to learning. Conclusions: According to the unit (grouping) the monads were the most abundant and according to the form, the prolate were more common and a third of the collected species presented pollen with ornamentation.